People of Walmart : targeting the world's largest retailer and its customers - Robson, Karen; Pitt, Leyland F. (London : SAGE Publications: SAGE Business Cases Originals, 2018)
This case explores the controversial viral website, peopleofwalmart.com, launched by Adam Kipple, Andrew Kipple, and Luke Wherry that mocks Walmart's shoppers and creates an online community for people who share similar senses of humor: The case illustrates how electronic word-of-mouth can take a controversial idea and skyrocket it into a viral website, however, not everybody appreciated the comedy or believed that exploiting people for cheap laughs was acceptable, particularly in those cases where people had been photographed without permission. In spite of this, the three founders created a successful, money-making platform. Issues regarding the future of the website, including: whether there is room for growth; whether it is ethical to make fun of overweight and badly dressed people; and, beyond that, whether it is ethical to make money out of making fun of people will be dealt with in this case. In addition, the case prompts students to think about the impact that the controversial website has on Walmart itself and encourages students to consider issues related to social media, ethics, and cyberbullying.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kipple, Adam; Kipple, Andrew; Wherry, Luke; Wal-Mart (Firm) -- Case studies; Business ethics -- Case studies; Cyberbullying -- Case studies